Psychometric Evaluation of Depression Component of Hospital Anxiety and Depression Scale (HADS-D) in People with Epilepsy in North Western Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Several studies, have been conducted to compare the efficacy of various screening tools in detection of depression among people with epilepsy (PWE); one recurrent tool in virtually all the studies is the Hospital Anxiety and Depression Scale (HADS) because of its wide popularity in general screening for depressive disorders. However, in recent times, its utility has been questioned. Psychometric studies of HADS-D in PWE in Nigeria is sparse, and hence the need for this study.Objective:To determine the psychometric properties of the HADS-D among PWE in Northwestern Nigeria.Materials and Methods:Using a cross-sectional study design, 255 participants were recruited for the study. Participants who met the inclusion criteria were consecutively recruited from patients with epilepsy attending the outpatient clinics of Health Centre Kumbotso and Aminu Kano Teaching Hospital (AKTH) psychiatry and neurology clinics. They all completed the HADS-D and a face-to-face psychiatric interview, using the Mini International Neuropsychiatric Interview (MINI). Analysis of data was done using Graph Pad Prism software (version 5.03, Graph Pad Software, Inc.CA 92037 USA). Ethical approval was obtained from the institutional review board of AKTH.Results:Two hundred and fifty-five participants comprising 147 (57.6%) males and 108 (42.4%) females were studied. Depressive symptoms were present in 20 (7.8%) and 52 (20.4%) participants as detected by HADS-D and MINI, respectively. Out of the 235 participants identified as noncases by HADS-D, 37 (15.7%) met the criteria for a depressive disorder using MINI. Psychometric parameters at 95% confidence interval of HADS-D obtained were as follows: sensitivity = 28.9% (17.1–44.1%), specificity = 97.5% (94.4–99.2%), positive predictive value = 75% (50.9–91.3%), negative predictive value = 84.3% (79.0–88.7%), and likelihood ratio = 11.7%.Conclusion:In conclusion, this study showed that HADS-D has low sensitivity and less utility in screening for depression among PWE.